1993
DOI: 10.1136/oem.50.4.368
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological performance and solvent exposure among car body repair shop workers.

Abstract: A cross sectional study to evaluate symptom reporting and neuropsychological test performance among a cohort of car body repair workers (n = 124) was performed using a computer-administered test system. Subjects with high and medium current exposures to solvent and paint (n = 39 and 32), and low exposure subjects who formerly painted (n = 29) reported significantly more acute and chronic neurological symptoms than did low exposure subjects with no history ofpainting (n = 24). Subjects with higher current expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

1996
1996
2001
2001

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 8 publications
(1 reference statement)
1
8
1
Order By: Relevance
“…Thus, xylenes were as commonly found as toluene in painting work in the present survey (Table 5). This observation is in agreement with the reports by Triebig et al (1992) on spray-painting work and Daniel et al (1993) on carbody repair work, where xylenes and other higher alkylbenzenes were the leading air pollutants. Kumai et al (1983) observed that n-hexane was the second most common solvent in adhesive preparations.…”
Section: Discussionsupporting
confidence: 94%
“…Thus, xylenes were as commonly found as toluene in painting work in the present survey (Table 5). This observation is in agreement with the reports by Triebig et al (1992) on spray-painting work and Daniel et al (1993) on carbody repair work, where xylenes and other higher alkylbenzenes were the leading air pollutants. Kumai et al (1983) observed that n-hexane was the second most common solvent in adhesive preparations.…”
Section: Discussionsupporting
confidence: 94%
“…There also was a tendency to poorer performance regarding¯uid intelligence and concentration. In contrast to previously reported ®ndings [7,13,15,17,38], there was no substantial dierence regarding short-term memory.…”
Section: Neuropsychologic Testscontrasting
confidence: 83%
“…In the study of U.S. car body repair workers (Daniell et al, 1993) the current exposure levels of painters and their median exposure years indicate that approximately half of the painters might be at risk for adverse CNS effects. Mental symptoms and poor test performance were found, especially among subjects 35 years old and older.…”
Section: Cross-sectional Studiesmentioning
confidence: 98%
“…Symptoms (reported only as ''night problems,'' ''confusion,'' and ''activity'') were not associated with exposure. Daniell et al (1993) examined 124 car body repair workers. The participation rate was approximately 65% for production workers.…”
Section: Cross-sectional Studiesmentioning
confidence: 99%